2021
DOI: 10.1007/s00438-021-01777-y
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide substitution in the coding region of Ogura male sterile gene, orf138, determines effectiveness of a fertility restorer gene, Rfo, in radish

Abstract: Cytoplasmic male sterility (CMS) observed in many plants leads defect in the production of functional pollen, while the expression of CMS is suppressed by a fertility restorer gene in the nuclear genome. Ogura CMS of radish is induced by a mitochondrial orf138, and a fertility restorer gene, Rfo, encodes a P-type PPR protein, ORF687, acting at the translational level. But, the exact function of ORF687 is still unclear. We found a Japanese variety showing male sterility even in the presence of Rfo. We examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…These data suggest that nucleotide substitutions at the cleavage site of CMS genes inhibit the suppression induced by the specific Rf gene. We recently found a similar relationship between the CMS gene (orf138) and the Rf genes in Ogura CMS of radish (Yamagishi et al 2021). ORF687 encoded by Rfo binds to orf138 mRNA, but a single nucleotide substitution of orf138 in the binding site diminished the effect of the Rfo gene by drastically decreasing the binding affinity of ORF687, and the male sterility phenotype was expressed despite the presence of Rfo.…”
Section: Sequence Variations Of Orf108mentioning
confidence: 75%
“…These data suggest that nucleotide substitutions at the cleavage site of CMS genes inhibit the suppression induced by the specific Rf gene. We recently found a similar relationship between the CMS gene (orf138) and the Rf genes in Ogura CMS of radish (Yamagishi et al 2021). ORF687 encoded by Rfo binds to orf138 mRNA, but a single nucleotide substitution of orf138 in the binding site diminished the effect of the Rfo gene by drastically decreasing the binding affinity of ORF687, and the male sterility phenotype was expressed despite the presence of Rfo.…”
Section: Sequence Variations Of Orf108mentioning
confidence: 75%
“…A new restorer gene of Ogura CMS, Rft, which was found in the Tomioka population of Japanese wild radish, was also a homolog of Rfo and had 19 SNPs compared with Rfo [ 50 ]. Yamagishi et al (2021) confirmed that Ogura CMS had a new fertility restorer gene, Rfs , which could restore the fertility of individuals by processing orf138 mRNA and was different from Rft [ 54 ].…”
Section: Mapping and Cloning Of Ogura Cms Fertility Restorer Genes In...mentioning
confidence: 99%
“…An allele sequence analysis of the fertility restorer gene revealed four substituted amino acids (the 118th, 153rd, 170th and 171st amino acids) in the second and third repeats of the PPR, suggesting an essential role in the fertility restoration of these domains formed by these repeats in the Rfo gene-encoding protein ORF687 [ 123 ]. Yamagishi et al (2021) and Imai et al (2002) also considered that the 118th and 153rd amino acids in ORF687 play a crucial role in fertility restoration [ 54 , 183 ]. By comparing the transcript sequences of rfo / rfo and Rfo / Rfo homozygote plants, it was found that four amino acids (the 176th to 179th amino acids) of the Rfo gene were essential, and the deletion of these four amino acids in the central region of the Rfo gene-encoding protein reduced fertility restoration ability [ 182 ].…”
Section: Mechanisms Of Ogura Cms Fertility Restorer Genes In Major Cr...mentioning
confidence: 99%
See 2 more Smart Citations